A resveratrol analog termed 3, 3′, 4, 4′, 5, 5′‐hexahydroxy‐trans‐stilbene is a potent HIV‐1 inhibitor. Issue 12 (9th June 2015) - Han, Ying‐Shan; Quashie, Peter K.; Mesplède, Thibault; Xu, Hongtao; Quan, Yudong; Jaeger, Walter; Szekeres, Thomas; Wainberg, Mark A.
<x xml:space="preserve">Abstract</x> HIV resistance to current anti‐HIV drugs and drug toxicity have created a need for new anti‐HIV agents. We have examined and characterized a synthetic resveratrol analog, termed 3, 3′, 4, 4′, 5, 5′‐hexahydroxy‐trans‐stilbene (M8), for potential anti‐HIV activity. Here, we demonstrate that M8 possesses potent anti‐HIV activity against several HIV variants with EC50 values in the low μM range. M8 was shown to act at a very early step of HIV entry prior to fusion to host cells. These results demonstrate that this novel resveratrol derivative possesses potent anti‐HIV‐1 activity and may have a mechanism of action that is different from current anti‐HIV‐1 drugs including entry inhibitors. Further structure‐guided design might lead to the development of newer improved resveratrol derivatives that could have value either in therapy or as microbicides to prevent the sexual transmission of HIV‐1. J. Med. Virol. 87:2054–2060, 2015. © 2015 Wiley Periodicals, Inc.